Multi-scale Study on Granular Materials using Discrete Element Method and Micromechanics - Benabbas, Ehsan (My University, 2025)
The mechanical behavior of granular materials is fundamentally governed by the evolution of their internal structures, including contact networks, force chains, and pore spaces. This thesis presents a comprehensive investigation into the relationship between these microstructural features and macroscopic responses under different loading conditions, using three-dimensional Discrete Element Method (DEM) simulations. Proportional stress and strain paths with constant Lode angles and dilatancy rates were employed to explore the evolution of fabric anisotropy within strong and weak contact sub-networks. The results reveal that while strong contact networks primarily align with stress states and carry most of the load, the weak networks evolve in response to deformation and dilatancy. At the critical state, both networks reach unique and consistent anisotropic configurations, highlighting the fabric-stress interdependence. Furthermore, by imposing different strain path constraints, the study uncovers a family of asymptotic states and confirms the uniqueness of the critical fabric envelope. On a broader scale, spatial and temporal heterogeneity within granular assemblies is examined, revealing how local variations in microstructural evolution drive the transition from uniform deformation to shear localization. This multi-scale analysis enhances our understanding of the micromechanics underlying granular deformation and the emergence of shear bands, offering new insights for constitutive modeling and practical applications in geomechanics.
Keywords: micromechanics; granular materials; fabric evolution; shear band